Analysis of the Structural Organisation of the Community of Large Birds of Prey in the Remdovsky Game Reserve - Vasily G. Pchelintsev; Vladimir V. Ivanovsky (Пернатые хищники и их охрана)
In this article, a statistical analysis of the structural organisation of the community of large birds of prey in the Game Reserve’s territory was carried out. This allowed us to determine the size of nesting territories of species that determine the conservation importance of the territory. The data obtained will enable us to extrapolate information on the numbers of Golden Eagles (Aquila chrysaetos), White-tailed Eagles (Haliaetus albicilla), and Ospreys (Pandion haliaetus) in regions rich in lakes and marshes in Russia and Belarus